ANAESTHETIC MANAGEMENT OF PEDIATRIC PATIENTS WITH MOYAMOYA DISEASE UNDERGOING REVASCULARIZATION SURGERY: A CASE SERIES (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Moyamoya disease is a rare, chronic, progressive cerebrovascular disorder characterized by stenosis of the intracranial internal carotid arteries and its branches with development of compensatory fragile collateral vessels. Aim: To highlight important anaesthetic considerations and perioperative management strategies in patients undergoing Encephaloduroarteriosynangiosis (EDAS PROCEDURE) for Moyamoya disease, with focus on minimizing complications and optimizing patient outcomes. Methods: In this case series ten paediatric patients aged 3-15 years diagnosed with moyamoya disease who underwent EDAS under general anaesthesia were included. In addition to standard ASA monitoring, invasive arterial pressure monitoring was performed. Ventilatory parameters were adjusted to maintain normocapnia. Data regarding preoperative and intraoperative hemodynamic parameters, duration of surgery and perioperative complications were recorded. Results: All patients presented with ischemic symptoms. Intraoperative hemodynamic stability was maintained in all patients with episodes of hypertension and tachycardia treated accordingly. Three patients developed transient hypotension after induction, which responded to fluid bolus and vasopressor therapy. The mean duration of surgery was 222.7 ± 26.02 minutes. One patient required postoperative ventilatory support. No patient developed postoperative neurological deficits. The mean ICU stay was 1.6 ± 0.69 days. Conclusion: Careful maintenance of normotension, normocapnia, normovolemia, and normothermia is essential for safe anaesthetic management in paediatric Moyamoya revascularization surgery.